Lead and Disrupt How to Solve the Innovator's Dilemma, Second Edition. - O'Reilly, Charles A., III (Stanford University Press, 2021)
Fully revised, this second edition offers a proven strategy for using ambidexterity to build incremental growth for mature organizations, and the flexibility to adapt in fast-changing environments.